The Traditional Islamic Curriculum of Pallidars in Malabar: A Content Analysis of ‘Min Nawabigi Ulama’i Malaibar’ - KP, Hassan Shareef; P, Shebeeb Khan (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan Jawa Timur, 2025)
The Muslim community of Malabar, South India has placed significant emphasis on Islamic education since the advent of Islam into the land. In order to impart Islamic education, Muslims of Kerala instituted different systems such as Ottupalli (kuttab, for basic learning of Islamic teachings), Pallidars (Mosque Centered Higher Learning System) in medieval periods. The article is a detailed academic study on the traditional Islamic curriculum of Pallidars in Malabar, focusing on the content analysis of the book ‘Min Nawabigi Ulama’i Malaibar’ by Sayyid Abdu-Rahman Al Azhari. ​ It explores the historical evolution of Islamic education in Malabar, the significance of Pallidars as mosque-based educational institutions, and the curricula that shaped traditional religious education in the region. ​ Key findings include the identification of three distinct curricula—Ma'bari, Fakhriyya, and Nizamiya—and their historical relevance. ​ The study also highlights the flexibility and accessibility of the curriculum of Pallidars education, its connection to global Islamic learning centers and its impact in shaping the curriculum. It emphasizes the need for further research into the medieval curriculum and its impact on contemporary Islamic education in Malabar. ​